ANALISIS BILANGAN PRIMA PADA JUMLAH AYAT AL-QUR’AN - Diana Putri; Nur Hamid (Nusantara Hasana Journal, 2026)
This study aims to analyze the numerical characteristics of the number of verses in all suras of the Quran based on the concept of prime numbers using a number theory approach. This study is a library research study using a descriptive analytical approach. The research data consists of the number of verses in 114 suras of the Quran sourced from the Indonesian Standard Quranic Manuscript published by the Ministry of Religious Affairs of the Republic of Indonesia, Improved Edition, 2017. Prime numbers were identified using the remainder (modulo) method, then analyzed through frequency of occurrence, descriptive statistics, and distribution patterns. Furthermore, a structural analysis of the ruku' (bowing) was conducted by comparing the Indonesian Standard Quranic Manuscript and the Holy Quranic Manuscript.The results show that 32 suras have verses that are prime numbers, while 82 suras have verses that are composite numbers. The prime numbers that appear as the number of verses in a surah are 3, 5, 7, 11, 13, 17, 19, 29, 31, 37, 43, 53, 59, 73, 83, 89, 109, and 227, with the prime number 11 having the highest frequency of occurrence. The results of the descriptive statistical analysis show an average value (mean) of 33.625, a median of 18, a mode of 11, a minimum value of 3, and a maximum value of 227. The analysis of the ruku' structure reveals that out of 114 surahs, 107 surahs have the same number of ruku' in both mushafs, while 7 surahs show differences in the number of ruku'. These differences do not reflect differences in content, number of verses, or the arrangement of the verses of the Qur'an, but rather represent variations in the system of dividing reading themes between mushafs. This research is expected to contribute to the development of interdisciplinary studies between mathematics and Qur'anic studies, as well as become a basis for further research that examines the numerical aspects of the Qur'an using other mathematical concepts.